Authigenic carbonate formation revealed by lipid biomarker inventory at hydrocarbon seeps: A case study from the Okinawa Trough. (March 2019) - Guan, Hongxiang; Sun, Zhilei; Mao, Shengyi; Xu, Lanfang; Cao, Hong; Geng, Wei; Xu, Cuiling; Zhang, Xianrong; Wu, Nengyou
Abstract: Authigenic carbonates were recovered from the northern Okinawa Trough at 540–700 m water depth. Development of microbial communities and seepage dynamics driving the precipitation of authigenic carbonates remains poorly constrained, even though the source of methane-rich fluids, formation of Fe-rich carbonates, and the potential driving forces were previously reported. Here, petrologic observations, stable carbon and oxygen isotopic compositions, mineralogy, and lipid inventories of authigenic carbonates from the northern Okinawa Trough were analyzed. The carbonate minerals were comprised predominantly of aragonite, high-magnesium calcite, and siderite. The presence of molecular fossils diagnostic for anaerobic methane oxidizing archaea (ANME) and sulfate-reducing bacteria (SRB) with pronounced 13 C depletions (as low as −134‰), together with highly negative δ 13 Ccarb values (as low as −55.8‰), suggest that the carbonates precipitated from anaerobic oxidation of methane (AOM) with microbial methane as the predominant carbon source. The difference between measured and calculated δ 18 Ocarb values (based on 0‰ of sea water δ 18 O vs V-SMOW) was higher than +3‰ in one of the carbonates (GGD16), reflecting an origin from gas hydrate dissociation. Most of the carbonates revealed δ 18 O offsets between measured and calculated values within +3‰, or a lower measured δ 18 O than calculated value, suggesting a mixture of methane-derived carbonates (low δ 13 C/high δ 18 O) and detrital origin carbonates (high δ 13 C/low δ 18 O). Biomarker patterns varied significantly among samples. A suite of 13 C-depleted biomarkers indicated the predominance of an ANME-1 assemblage for all samples, suggesting carbonates formed at low to medium methane flux. The predominance of ANME-1, abundant detrital minerals, and allochthonous biomarkers, as well as low carbonate contents indicate that most samples formed at greater depth within the sediment column. Only one carbonate sample in this study is interpreted to have precipitated at relatively shallower depth, as indicated by the occurrence of crocetane, dominance of aragonite, and higher overall carbonate content. Highlights: Lipid biomarker patterns of the Okinawa Trough carbonates were studied. Carbonates formed from low to medium methane flux as revealed by lipids of ANME-1. Most carbonates formed at greater depth within the sediment column. One carbonate is interpreted to have precipitated at relatively shallower depth.